2011
DOI: 10.1017/s1092852912000338
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Bipolar Disorder: Recent Findings, Deleterious Effects But Promise for Future Therapeutics

Abstract: An emerging body of evidence points to impairments in neuroplasticity, cell resilience, and neuronal survival as major pathophysiological mechanisms in bipolar disorder. Neuronal survival is influenced by several factors including an orchestrated action of neurotransmitters, hormones, and neurotrophins. Patients with bipolar disorder exhibit increased peripheral level of inflammatory mediators such as cytokines, mainly during acute mood episodes. These mediators interact in several pathways involved in regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 159 publications
(204 reference statements)
1
29
0
Order By: Relevance
“…In contrast to acute neuroinflammatory conditions in MDD, however, astroglia and microglia do not proliferate (Najjar et al, 2013), consistent with a continuous, low grade inflammation. As for BPD, peripheral IL-2, IL-4 and IL-6 are found to be increased in manic episodes (Brietzke et al, 2011) whereas another meta-analysis revealed significant elevation of soluble interleukin (IL)-2 receptor (sIL-2R), TNF-a, soluble tumor necrosis factor receptor type 1 (sTNFR1) and soluble interleukin (IL)-6 receptor (sIL-6R) (Munkholm et al, 2013). In the case of schizophrenia, TNF-a, IFN-g, IL-12 and IL-2 are consistently elevated in chronic schizophrenic patients, while IL-1b, IL-6 and TGF-b correlate positively with disease activity (Miller et al, 2011).…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 92%
“…In contrast to acute neuroinflammatory conditions in MDD, however, astroglia and microglia do not proliferate (Najjar et al, 2013), consistent with a continuous, low grade inflammation. As for BPD, peripheral IL-2, IL-4 and IL-6 are found to be increased in manic episodes (Brietzke et al, 2011) whereas another meta-analysis revealed significant elevation of soluble interleukin (IL)-2 receptor (sIL-2R), TNF-a, soluble tumor necrosis factor receptor type 1 (sTNFR1) and soluble interleukin (IL)-6 receptor (sIL-6R) (Munkholm et al, 2013). In the case of schizophrenia, TNF-a, IFN-g, IL-12 and IL-2 are consistently elevated in chronic schizophrenic patients, while IL-1b, IL-6 and TGF-b correlate positively with disease activity (Miller et al, 2011).…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 92%
“…Elevated levels of cytokines are evident in the peripheral blood of schizophrenia and bipolar disorder patients, relative to healthy controls (Kunze et al 2013;Kim et al 2007). Specifically, increased levels of serum interleukin (IL)-1, IL-2, IL6 and tumour necrosis factor-alpha (TNF-a) have been found in schizophrenia (Potvin et al 2008;Theodoropoulou et al 2001), and elevated plasma cytokine levels of IL-2, IL-4, IL-6, IL-8 and TNF-a are also evident in bipolar disorder (Brietzke et al 2011;O'Brien et al 2006). Chronically elevated levels of cytokines can cause increased oxidative stress and alter neuronal function (Brietzke et al 2011;Schafers and Sorkin 2008), and may also contribute to the grey matter loss seen in schizophrenia and bipolar disorder (Viviani et al 2004).…”
Section: Pro-inflammatory Markers In Schizophrenia and Bipolar Disordermentioning
confidence: 99%
“…Cerebro-spinal fluid norepinephrine metabolite (3-methoxy-4-hydroxyphenylglycol (MHPG) is elevated in mania patients compared to the dopamine metabolite, homovanillic acid (HVA) or the serotonin metabolite, 5-hydroxyindoleacetic acid (HIAA) implying an excessive, abnormal noradrenergic activity in mania (Swan et al, 1983). Higher urinary catecholamine concentration in adulthood predicts higher levels of drug use (Brody et al, 2014). Levels of MHPG are decreased by lithium (Ostrow et al, 1984).…”
Section: Noradrenergic Mechanisms In Insulin Resistance Substance Usmentioning
confidence: 99%